Inovasi Modul Digital Interaktif Berbasis RME dengan Representasi Matematis pada Materi Lingkaran Kelas XI - Fachmi, Rahma Fadhila Nuriya; Agustina, Lady (Universitas Muhammadiyah Gresik, 2025)
Abstract This study aims to develop an interactive digital module based on Realistic Mathematics Education (RME) with mathematical representations for circle material for eleventh-grade students. The Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) was employed. The module, developed as a website, includes interactive features such as videos, GeoGebra simulations, and game-based exercises. Validation by material and media experts yielded